Formation establishment for GEO satellite beams monitoring using controlled regressive orbits. (September 2018) - Liang, Jun; Yang, Zhen; Zhang, Jin; Luo, Ya-zhong
Abstract: This paper presents the optimization method and results of National University of Defense Technology for the problem A of the 9 t h China trajectory optimization competition (CTOC9). An effective optimization approach using controlled regressive orbits are developed to design the three-satellite formation-flying trajectory for monitoring the beams of 18 GEO satellites. Firstly, a leader-follower formation based on the energy matching condition under J 2 perturbation is used to keep the formation configuration stable for long-term flight mission. Secondly, the optimal formation-flying trajectory is obtained to minimize the mission time by solving the established optimization model for maximizing the minimum monitoring profit of all GEO satellites. Finally, the controlled regressive orbits with multiple flight phases are designed to meet the fuel constraints according to the orbital drift law under J 2 perturbation, and a multi-impulse, perturbed orbital targeting technique is employed to connect the neighboring flight phases. The improved results show that it takes only 20.568 days to complete the mission, indicating that the proposed method performs particularly well on this problem. Moreover, the proposed method can be potentially used in the practical engineering due to its simplicity in optimization calculation and orbital maneuvering strategy. Highlights: A stable configuration is used in the design of formation-flying trajectory. A trajectory optimization model is established to minimize the mission time. Controlled regressive orbits are developed for GEO satellite beams monitoring.